(untitled) (Physical Sciences and Technology, 2018)
We analyze the Vlasov dispersion relation for Yukawa plasmas in three dimensions for the purpose of identifying coupling parameter domains where the Vlasov approach is justified and the existence of a well-developed RPA type collective excitation is allowed. We establish a rigorous lower bound for the coupling parameter, below which there can be no real solution to the Vlasov dispersion relation. In the coupling domain, where weakly damped solutions do exist, we have focused on the long-wavelength acoustic regime where we establish more restrictive estimates for the lower bound of the coupling parameter. We also derive a general formula for the corresponding acoustic phase velocity, valid over a wide range of coupling parameter/screening parameter ratios above the lower bound. We conclude that the Vlasov approach is tenable only above a critical coupling value. Comparison with Molecular Dynamics simulation results further highlights the limitations of the Vlasov approximation for weakly coupled Yukawa plasmas.